Սիմոն Կրկյաշարյան' պատմաբանը և թարգմանիչը (100-ամյակի առթիվ) - Դոլուխանյան, Աելիտա; Վարդումյան, Գոհար (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Armenian historian and translator Simon Krkyasharyan was born in 1923, on December 7, in Athens, where his parents had taken refuge from the Hachn city of Cilician Armenia. He received his initial education at the local Armenian school, then at the Greek gymnasium. One of the bright pages of his life in Greece was active participation in the Resistance movement in 1941-1945. In 1947, leaving his studies halfway, S. Krkyasharyan immigrated to Armenia. In 1950 he studied at Faculty of History of the Pedagogical Institute named after Kh. Abovyan. In 1959, he was admitted to postgraduate courses at the Institute of History of the Academy of Sciences and was assigned to the Department of History of Greece and Rome at the Faculty of History of Leningrad University. His teachers were such famous scientists as H. Orbeli, B. Piotrovsky, V. Struve and others. After returning, he started working at the Institute of History of the Academy of Sciences of Armenia. In 1966-1996 he was a lecturer at the Yerevan State University, in 1976-1992 at the Gevorgian Seminary of St. Ejmiadzin.S. Krkyasharyan's range of scientific interests is wide, embracing the history of Hellenistic cities, the state structure of ancient Armenia, social-political history, Armenian-Greek, Armenian-Roman, Armenian-Persian relations, chronologically covering an entire millennium (VI ce. BC – V ce. AD), until the fall of the Arshakuni (Arsacid) kingdom of Great Armenia. His monograph work "Episodes of the History of Ancient Armenia and Cities of Asia Minor" (Yerevan, 1970) and numerous articles are especially valuable. In 1963 he defended his candidate thesis on the topic "Relationships of Hellenistic kings with the cities of Asia Minor and Armenia", in 1980 – the doctorate thesis – "The State Structure of Ancient Armenia". In 2000 was elected corresponding member of RA NAS.
Keywords: Կենսագրություն; Պատմություն